Communication Across Nations - Lopusanova, Jana (Communications - Scientific letters of the University of Zilina, 2010)
These days goods, capital, and labor move freely across borders. During the last forty years international trade has increased by 1500 % as tariffs have fallen from 50 % to less than 5 %. That is why multinational companies like Exxon do two-thirds of their business outside the US and components for the new Ford come from fifteen different countries. The management of global companies as well as the management of brands internationally has partly become a cross-cultural issue where communication across nations takes the crucial role on the way to success.